Implementasi Nilai-Nilai Pendidikan Karakter Peserta Didik pada Era Society 5.0 di Madrasah Aliyah Pondok Pesantren Yasrib Lapajung Watansoppeng - Muhammad Muhaimin; Muhammad Amri; Muhammad Rusmin B (Universitas Islam Negeri Alauddin Makassar, 2024)
This research aims: 1) to determine the planning of character education values for students in the era of society 5.0 at Madrasah Aliyah Pondok Pesantren Yasrib Lapajung Watansoppeng, 2) to identify the implementation of character education values for students in the era of society 5.0 at Madrasah Aliyah Pondok Pesantren Yasrib Lapajung Watansoppeng, 3) to assess the evaluation of character education values for students in the era of society 5.0 at Madrasah Aliyah Pondok Pesantren Yasrib Lapajung Watansoppeng. This research is qualitative in nature and conducted at Madrasah Aliyah Pondok Pesantren Yasrib Lapajung Watansoppeng. The data sources are the school principal, educators, and students. Data collection methods include observation, interviews, and documentation. The research instruments consist of observation guidelines and interview guidelines, with data analysis involving data reduction, data display, conclusion drawing, and verification. Data validity is ensured through triangulation. The findings of this research reveal that; 1) Planning for character education values for students in the era of society 5.0 at Madrasah Aliyah Pondok Pesantren Yasrib Lapajung Watansoppeng is very good, with planning conducted through meetings involving all educators in the planning process; 2) The implementation of character education values for students in the era of society 5.0 at Madrasah Aliyah Pondok Pesantren Yasrib Lapajung Watansoppeng, particularly in terms of religious, social care, creativity, curiosity, peace-loving, and friendliness, can be considered suboptimal, as the implementation does not align with the previous planning; 3) Evaluation of character education values for students in the era of society 5.0 at Madrasah Aliyah Pondok Pesantren Yasrib Lapajung Watansoppeng. The evaluation conducted by the madrasah and educators has been performed well to assess the extent to which the implementation of character education values can be realized by students both inside and outside the classroom.